Determination of Cr, Cd, Sn, and Pb in Selected Herbal Products Available in Philippine Markets - De Vera, Joan S.; Quirit, Leni B.; Rodriguez, Irene B. (Science Diliman: A Journal of Pure and Applied Sciences, 2017)
The growing popularity of herbal products in the Philippines makes it imperative to monitor and ensure safety of consumers from metal contaminants. In this study, trace concentrations of Cr, Cd, Sn, and Pb in herbal products were simultaneously measured using a microwaveassisted digestion as sample pre-treatment and inductively coupled plasma mass spectrometry (ICP-MS) for elemental detection. Using the optimized method, recoveries of ERM CD281, the primary cer t i f ied reference material (CRM) used, were found to be between 80-89%, and the method detection limits (MDL) for Cr, Cd, Sn, and Pb were 0.15, 0.07, 0.3, and 0.14 μg/L, respectively. The linear ranges for Cr and other elements (Cd, Sn, and Pb) were 0.01-500 and 0.01-50 μg/L, respectively. All correlation coeff icients were 0.9999 or better. Most of the products tested had measurable trace metal concentrations, which were below the suggested maximum limits in herbal products. However, one product derived from mangosteen exceeded the limit for Cd (0.42 mg/kg). Subsequent analysis of metal content in tea infusions showed that only a small fraction of metals may leach out, suggesting that consumption of tea infusions pose lesser risks. The order of abundance of metals found in herbal products was Cr>Pb>Cd>Sn. The variability of metal concentrations in herbal products underlines the fact that many plant ingredients are susceptible to contamination, and quality control during processing must be improved to minimize the possibility of contamination. The results of this study suggest that vigilant monitoring of herbal products is imperative to avoid exposure to trace metal contamination. Keywords: Trace metal, ICP-MS, microwave digestion, herbal product contamination, herbal product safey